Construction of organizational culture for ideal performance of Islamic-based junior high schools in Indonesia - Muhammad Anggung Manumanoso Prasetyo; Nurul Fadhillah (UIN Raden Mas Said Surakarta, 2022)
The deficiency of Islamic-based schools (called as Pesantren in Indonesia) in science requires adjustment. In this sector, Indonesian government is present through the implementation of the Islamic-based boarding Junior High Schools (henceforth SMP-BP) program, which was established by the Ministry of Education and Culture to equip students with intellectual, moral, and spiritual balances. However, there is still a need for constructing a framework of organizational culture to enhance the efficacy of the program. Hence, the present study delves into a framework of organizational culture for ideal performance of and the efficacy of education process in Pesantren. This study was based in two SMP-BPs in Aceh, a province of Indonesia (e.g. Al Mujaddid and Darul Amin), and was conducted by following the procedure of descriptive research under qualitative design. The required data were gathered using interviews from a total of 12 informants consisting of school principal, coordinator of the program, and teachers. The data were further analyzed by following Miles and Huberman’s stages of qualitative data analysis comprising coding, presentation, and conclusion drawing. The results revealed that the construction of organizational culture for an ideal performance of Pesantren in Indonesia encompassed four key dimensions, i.e. (1) establishing organizational behavior standards, (2) increasing the stability of organization’s social system, (3) revitalizing school management, and (4) developing human resources. This study contributes to equipping Pesantren stakeholders with awareness and willingness to improve the efficacy of Islamic-based school performance in Indonesia. Future research is directed to efforts of fostering dynamic organization culture and school management both cultural and philosophical education.